The genomic epidemiology of Neisseria meningitidis carriage from a randomised controlled trial of 4CMenB vaccination in an asymptomatic adolescent populationResearch in context - Lex E.X. Leong; Rosa C. Coldbeck-Shackley; Mark McMillan; Holly B. Bratcher; Mark Turra; Andrew Lawrence; Charlene Kahler; Martin C.J. Maiden; Geraint B. Rogers; Helen Marshall (Elsevier, 2024)
Summary: Background: Oropharyngeal carriage of Neisseria meningitidis is frequent during adolescence, representing a major source of invasive meningococcal disease. This study examined the impact of a serogroup B vaccination (Bexsero, GSK 4CMenB) programme on adolescent N. meningitidis carriage using genomic data. Methods: A total 34,489 oropharyngeal samples were collected as part of a state-wide cluster randomised-controlled trial in South Australia during 2017 and 2018 (NCT03089086). Samples were screened for the presence of N. meningitidis DNA by porA PCR prior to culture. Whole genome sequencing was performed on all 1772 N. meningitidis culture isolates and their genomes were analysed. Findings: Unencapsulated meningococci were predominant at baseline (36.3% of isolates), followed by MenB (31.0%), and MenY (20.5%). Most MenB were ST-6058 from hyperinvasive cc41/44, or ST-32 and ST-2870 from cc32. For MenY, ST-23 and ST-1655 from cc23 were prevalent. Meningococcal carriage was mostly unchanged due to the vaccination programme; however, a significant reduction in ST-53 capsule-null meningococci prevalence was observed in 2018 compared to 2017 (OR = 0.52; 95% CI: 0.30-0.87, p = 0.0106). This effect was larger in the vaccinated compared to the control group (OR = 0.37; 95% CI: 0.12-0.98, p = 0.0368). Interpretation: While deployment of the 4CMenB vaccination did not alter the carriage of hyperinvasive MenB in the vaccinated population, it altered the carriage of other N. meningitidis sequence types following the vaccination program. Our findings suggest 4CMenB vaccination is unlikely to reduce transmission of hyperinvasive N. meningitidis strains and therefore ongoing targeted vaccination is likely a more effective public health intervention. Funding: This work was funded by GlaxoSmithKline Biologicals SA.